Development and Quality of Report Pouch Processed Ramasseri Idli - KRISHNAPRABHA RAJANI S ROHITHA P.R; Dr. Sudheer K.P (Guide) (Tavanur 2017 Department of Food and Agricultural Process Engineering)
Development and Quality of Report Pouch Processed Ramasseri Idli
Development and Quality of Report Pouch Processed Ramasseri Idli